ENVIRONMENTAL AWARENESS OF UNDERGRADUATE STUDENTS IN IMPHAL EAST AND IMPHAL WEST, MANIPUR - 1. Thongram Anilkumar Singh , 2. Chongtham Beda Devi (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
The study aims to evaluate undergraduate students’ awareness level in the peripheral state of Manipur in India. Environmental issues and problems have been a topic of concern in the world’s current trends. The study’s main objectives are to explore the levels of awareness of undergraduate students in Imphal East and Imphal West districts in 4 different colleges in Manipur and examine the awareness levels based on gender and residence of the students. A descriptive survey method was employed using a simple random sampling technique to select 200 undergraduate students. A Standardized scale, “Environment Awareness Ability Measure,” developed by Praveen Kumar Jha (1998), is used to measure the environmental awareness of undergraduate students of 4 colleges affiliated with Manipur University with 200 undergraduate students by using a simple random sampling method. The result reveals that the majority of the undergraduate students, that is, 53%, possess an above-average level of environmental awareness; there is a significant difference between male and female undergraduate students regarding their environmental awareness, and the study also reveals that students residing in Rural and Urban have a significant difference in their environmental awareness.